A Study on Pain relief effects and Allergic responses for the Osteoarthritis of the knee joint Between Sweet Bee Venom and Bee Venom Pharmacopuncture - Na Won Min; Lee Sung Young; Jang Eun Ha; Kim Sung Chul; Moon Hyung Cheol; Kim Seong Min; Yoon Chang Ho; Jun Bong Hwan (Korean Pharmacopuncture Institute, 2007)
Objectives : To verify pain relief effects and allergy inhibitory action for the osteoarthritis of the knee joint in Sweet Bee Venom in which allergy causing enzyme is removed. Methods : We randomly allocated 36 participants to treatment group Sweet Bee Venom and Bee Venom. Outcomes on pain reduction were measured by 100mm VAS(Visual Analog Scale). And we recorded into details allergic responses during Pharmacopuncture treatment. Results : Whole body condition and pain rate through VAS measurement were improved significantly in 2 weeks. We could get difference in pain score of two Pharmacopuncture groups significantly in 2 weeks. BV group showed superior reduction in pain compared to the Sweet BV group. But we could not get difference in whole score of two pharmacopuncture groups significantly. On the other hand other allergic responses such as edema, itchiness, pain were significantly lower in the Sweet BV group.